Lim Goh Tong Memorial Hall Opens - The Sun, Pauline Puah (2008)
The Lim Goh Tong Memorial Hall built in remembrance of Genting Higlands founder, the late Tan Sri Dr. Lim Goh Tong, was opened on friday.